2020
DOI: 10.15517/rbt.v68is2.44331
|View full text |Cite
|
Sign up to set email alerts
|

Diversity patterns of aquatic macroinvertebrates in a tropical high-Andean catchment

Abstract: Introduction: Glacierised catchments are remote and hostile environments, in which streams from different water sources (e.g., glacier melt, rain/snowmelt, groundwater) converge, creating a complex mosaic of stream sites with varying levels of glacial influence and environmental conditions. This environmental heterogeneity, in turn, influences the assemblage and composition of aquatic communities and produces complex patterns of species diversity at the catchment scale. Objectives: In this contribution, we ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…turbidity in the stream) linked to glacial influence will discriminate specialised species adapted to these specific habitats (Milner et al 2008). For example, in agreement with Espinosa et al (2020) at the Antisana volcano, certain aquatic larvae from the beetle families Dytiscidae and Staphylinidae were exclusively observed in the studied glacier‐fed stream, and not in a neighbouring groundwater‐fed stream (unpublished observations from the same sampling dates).…”
Section: Discussionsupporting
confidence: 90%
“…turbidity in the stream) linked to glacial influence will discriminate specialised species adapted to these specific habitats (Milner et al 2008). For example, in agreement with Espinosa et al (2020) at the Antisana volcano, certain aquatic larvae from the beetle families Dytiscidae and Staphylinidae were exclusively observed in the studied glacier‐fed stream, and not in a neighbouring groundwater‐fed stream (unpublished observations from the same sampling dates).…”
Section: Discussionsupporting
confidence: 90%
“…FFG richness was less affected by GI, since the fewer taxa present at higher GI represented more feeding guilds. The hump-shaped pattern in taxon richness has been found in previous studies from the same region [38,68]. Functional diversity of aquatic macroinvertebrates varies with land cover type in alpine streams [69], and decreases with increasing glacier cover in Arctic-temperate catchment [9].…”
Section: Functional Feeding Group Affiliation and Distribution Patternssupporting
confidence: 66%
“…Relatively little is known about the ecology of glacier-fed streams in tropical mountains, but overall spatial patterns of macroinvertebrate community structure and diversity seem to follow what is known from temperate-Arctic latitudes [36][37][38]. Additionally, prominent functional traits such as feeding habits and the relationships between functional traits and glacial influence seem to be largely comparable between temperate and tropical glacier-fed streams, with functional diversity lower than expected from a null model close to glaciers [39].…”
Section: Introductionmentioning
confidence: 83%
“…Our results also showed the diversity and density decreased at sites C-E of the grazing stream when grazing intensity increased. However, there were some taxa sensitive to environmental changes such as EPT species in the grazing stream [62]. Our findings showed that EPT species were also present in the grazing stream, but they decreased with the presence of grazing disturbance.…”
Section: The Effects Of Three Disturbances On Macroinvertebrate Commu...mentioning
confidence: 53%